EVALUATION OF METHADONE DOSING IN THE USE OF FIRST-LINE AND SECOND-LINE ANTIRETROVIRALS AND NON-ANTIRETROVIRALS IN DR. HASAN SADIKIN HOSPITAL BANDUNG - Marsya Dwi Putri, Meydina
The increase in Human Immunodeficiency Virus (HIV) cases among IDUs (injecting drug users), especially opioids, is strongly associated with the increasing the prevalence of drug use within communities, especially via injection. People Who Inject Drugs (PWID) living with HIV are typically prescribed antiretroviral (ARV) drugs alongside methadone maintenance therapy. Problems can arise when administering these treatments concurrently as both methadone and certain ARV drugs are metabolized by the CYP3A4 enzyme, potentially impacting methadone dosing. This study aimed to determine the dose profile of methadone in PLWHA (People With HIV/AIDS) IDUs and evaluate the effects of first-line and second-line ARV therapies on methadone dosage. The population studied were patients who were undergoing methadone therapy at the Methadone Clinic of Dr. Hasan Sadikin Hospital Bandung. The study was conducted quantitatively with a cross-sectional design using patient medical record data for the period January – March 2024, both receiving ARV therapy and not, while undergoing methadone maintenance therapy at the ruminal stage. The study was conducted on May 29 - June 10, 2024. The data in this study were demographic characteristics (age, latest education, occupation, gender, type of drug), average dose of methadone for non-ARV patients in the maintenance stage, average methadone dose of ARV patients at initiation and maintenance stage, and average dose of ARV combination. The results showed that the dose of methadone at the initiation stage (15-60 mg) was significantly different (p=0.00) from the average doses over the last 3 months at the maintenance stage (23-177 mg). Furthermore, methadone dosages for ARV patients (23-177 mg) were significantly different (p=0.02) from those for non-ARV patients (3-125 mg). The ARV combination that caused the lowest increase in methadone dose was the combination of lamivudin/zidovudin+efaviren (2%), while the one that caused the highest increase in methadone dose was the combination of lopinavir/ritonavir+dolutegravir (17,5%).